Methods for analysis and testing of coal and coke Sec.107.3. Caking and swelling properties of coal. Determination of swelling properties using a dilatometer (BSI, 1990)
Coal products, Coke, Coal, Testing conditions, Fossil fuels, Fuels, Solid fuels, Swelling, Dimensional changes, Test equipment, Dilatometry, Heating tests, Thermal testing, Calibration, Accuracy, Reproducibility, Specimen preparation